INOVASI PEMPEK BARAKUDA DENGAN SUBTITUSI TEPUNG GARUT DAN PENAMBAHAN EKSTRAK DAUN JELATANG (Urtica dioica) - Sania Nur Azizah; Ita Fatkhur Romadhoni; Qorry' Aina; Mafisa Restami (Kampus Akademik Publiser, 2026)
Pempek is a traditional Indonesian fish-based product commonly prepared using Spanish mackerel as the primary raw material. The relatively high price of Spanish mackerel encourages the utilization of barracuda fish as a more economical alternative while maintaining its nutritional value. This study aimed to evaluate the effect of arrowroot flour substitution and nettle leaf extract addition on the sensory characteristics of barracuda fish pempek, determine the best formulation based on panelists' acceptance, and analyze the nutritional composition of the selected product. An experimental method with a factorial design was employed using three levels of arrowroot flour substitution (10%, 20%, and 30%) and two levels of nettle leaf extract addition (2% and 4%). Sensory evaluation was conducted by 35 panelists consisting of three trained and thirty-two semi-trained panelists to assess color, aroma, texture, taste, and overall acceptability. The data were analyzed using Two-Way Analysis of Variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results demonstrated that the combination of arrowroot flour substitution and nettle leaf extract significantly affected all sensory attributes (p<0.05). The P2G2 formulation, containing 20% arrowroot flour substitution and 4% nettle leaf extract, was identified as the optimum formulation with the highest overall acceptability score (3.80). This formulation exhibited desirable color, pleasant aroma, chewy texture, and savory taste preferred by the panelists. Proximate analysis of the selected product showed 411.77 kcal of energy, 72.915% carbohydrates, 17.225% protein, 5.69% fat, 52.855% moisture, and 1.315% ash per 100 g of product. The findings indicate that the incorporation of arrowroot flour and nettle leaf extract can improve the sensory quality of barracuda fish pempek while producing a nutritious local food product with potential as a functional food.